Strands in literary English-to-Lithuanian translation criticizm in Lithuania since 1990 - Šalčiūtė-Čivilienė, Gabrielė (Lietuvių kalba, 2011)
The current article surveys the scope and the major assumptions of domestic critical discourse on literary translation from English into Lithuanian since 1990. The market conditions have changed enormously since Lithuania moved to a market-free economy and chose a democratic ruling system, thus affecting all the spheres of culture, including literary and translation production.  Critical evaluation of quality, adequacy, norms and other related issues of literary translation does not seem to keep pace with a rapid production of literary translation. Since the publication of a textbook on translation by Armalytė and Pažūsis (1990), no other fundamental work has been published in this area. The current review of critical discourse on literary translation includes two major sources of periodical literature – that is, academic papers in scholarly magazines and critical reviews in newspapers and magazines targeting wider readership. The major aim of this review is to identify the potentials and limits of national critical discourse by examining topic areas, critical standards applied to the evaluation of actual translations, and some metadiscoursal issues.
Keywords: none